A lightweight and provable secure identity-based generalized proxy signcryption (IBGPS) scheme for Industrial Internet of Things (IIoT). (May 2021) - Hussain, Saddam; Ullah, Insaf; Khattak, Hizbullah; Khan, Muhammad Asghar; Chen, Chien-Ming; Kumari, Saru
Abstract: Recently, the Industrial Internet of Things (IIoT) has become increasingly important for applications in the industry. IIoT has essentially become a prime security focus for implementing secure communication. Among the available cryptographic tools, identity-based signcryption provide a sound solution to fulfill the security requirement of IIoT. On the other hand a generalized proxy signcryption can work adaptively as proxy signature and proxy signcryption using a single algorithm. In order to accomplish effective and on-time communication whenever the manager of the company went out for a usual business trip or an IIoT device which has lack of resources, then it must need to delegate her/his signcryption rights to their subordinates (proxy agents/device). For this purpose, to make the delegation procedure more efficient and reliable, we proposed a lightweight identity-based generalized proxy signcryption (IBGPS) scheme for IIoT. The IBGPS scheme is provably secure in terms of indistinguishability against adaptive chosen ciphertext attack ( IND  −  IBGPS  −  CCA ) and existential unforgeable against a possible adaptive chosen message attack ( EUF  −  IBGPS  −  CMA ) under Hyperelliptic Curve Decisional Diffie-Hellman problem ( HEDHP ) and Hyperelliptic Curve Discrete Logarithm problem ( HECDLP ) in the random oracle model. Furthermore the performance evaluation in terms of computation and communication costs shows that the IBGPS scheme is more effective than the existing schemes.